Comparative analysis of 5 lung cancer natural history and screening models that reproduce outcomes of the NLST and PLCO trials. Issue 11 (27th February 2014) - Meza, Rafael; ten Haaf, Kevin; Kong, Chung Yin; Erdogan, Ayca; Black, William C.; Tammemagi, Martin C.; Choi, Sung Eun; Jeon, Jihyoun; Han, Summer S.; Munshi, Vidit; van Rosmalen, Joost; Pinsky, Paul; et al.
Abstract : BACKGROUND: The National Lung Screening Trial (NLST) demonstrated that low‐dose computed tomography screening is an effective way of reducing lung cancer (LC) mortality. However, optimal screening strategies have not been determined to date and it is uncertain whether lighter smokers than those examined in the NLST may also benefit from screening. To address these questions, it is necessary to first develop LC natural history models that can reproduce NLST outcomes and simulate screening programs at the population level. METHODS: Five independent LC screening models were developed using common inputs and calibration targets derived from the NLST and the Prostate, Lung, Colorectal and Ovarian Cancer Screening Trial (PLCO). Imputation of missing information regarding smoking, histology, and stage of disease for a small percentage of individuals and diagnosed LCs in both trials was performed. Models were calibrated to LC incidence, mortality, or both outcomes simultaneously. RESULTS: Initially, all models were calibrated to the NLST and validated against PLCO. Models were found to validate well against individuals in PLCO who would have been eligible for the NLST. However, all models required further calibration to PLCO to adequately capture LC outcomes in PLCO never‐smokers and light smokers. Final versions of all models produced incidence and mortality outcomes in the presence and absence of screening that were consistent with both trials. CONCLUSIONS: The authors developed 5 distinct LC screening simulation models based on the evidence in the NLST and PLCO. The results of their analyses demonstrated that the NLST and PLCO have produced consistent results. The resulting models can be important tools to generate additional evidence to determine the effectiveness of lung cancer screening strategies using low‐dose computed tomography. Cancer 2014;120:1713–1724 . © 2014 American Cancer Society . Abstract : Five lung cancer natural history models demonstrated that the National Lung Screening Trial and Prostate, Lung, Colorectal and Ovarian Cancer Screening Trial have produced consistent results. The resulting models can be important tools to assess the effectiveness of lung cancer screening strategies using low‐dose computed tomography.